(untitled) (IPS Journal of Nutrition and Food Science, 2025)
Date syrup offered several important advantages including; wide consumption, being a natural sweetener, rich flavor profile, natural energy source, potential health benefits, versatile culinary uses and it is highly palatable and acceptable in most countries. This study was conducted to investigated the quality assessment and sensory evaluation of syrup produced from date fruits. The date fruits were pitted, soaked, sieved, blended and heated at different temperatures (50 °C, 70 °C, 90 °C, and 100 °C). The proximate, mineral composition, color index, microbial activities as well as physico chemical properties of the date syrup were examined while panelists were assigned to assess the date syrup samples. Colour index showed that L* values of the samples ranged from (5.29±0.00) to (21.27±0.04) also a* values of the samples ranged from (2.73±0.02) to (5.74±1.71) while b* values ranged from (1.14±0.02) to (4.23±0.00). The results of the proximate composition for the moisture content ranged from (19.34±0.08) % to (61.57±0.02) % which showed that the temperature at which the syrups were heated had significant (p<0.05) positive effects on the syrup. The protein content ranged from (2.92±0.01) % to (1.24±0.04) % due to the boiling temperature and duration of the syrup. Meanwhile, the mineral compositions of the syrups revealed that the syrup contained high amount of Na, K, Ca, Mg and also a fair amount of trace elements like Fe, Cd, Zn and P. No panelist showed a total dislike for the taste of any of the samples. The sample heated at 100 °C was the most preferred sample in terms of appearance, taste, flavor, consistency and general acceptability. Hence, the research provides valuable insights into the overall quality and consumer acceptability of date fruit syrup, contributing to its understanding and potential applications in the food industry.